Utility of cell-based vaccines as cancer therapy: Systematic review and meta-analysis - Ankur Tiwari; Karl Alcover; Elizabeth Carpenter; Katryna Thomas; Julia Krum; Alexander Nissen; Spencer Van Decar; Todd Smolinsky; Franklin Valdera; Timothy Vreeland; Markus Lacher; Giuseppe Del Priore; et al. (Taylor & Francis Group, 2024)
ABSTRACTCell-based therapeutic cancer vaccines use autologous patient-derived tumor cells, allogeneic cancer cell lines or autologous antigen presenting cells to mimic the natural immune process and stimulate an adaptive immune response against tumor antigens. The primary objective of this study is to perform a systematic literature review with an embedded meta-analysis of all published Phase 2 and 3 clinical trials of cell-based cancer vaccines in human subjects. The secondary objective of this study is to review trials demonstrating biological activity of cell-based cancer vaccines that could uncover additional hypotheses, which could be used in the design of future studies. We performed the systematic review and meta-analysis according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The final review included 36 studies − 16 single-arm studies, and 20 controlled trials. Our systematic review of the existing literature revealed largely negative trials and our meta-analysis did not show evidence of clinical benefit from cell-based cancer-vaccines. However, as we looked beyond the stringent inclusion criteria of our systematic review, we identified significant examples of biological activity of cell-based cancer vaccines that are worth highlighting. In conclusion, the existing literature on cell-based cancer vaccines is highly variable in terms of cancer type, vaccine therapies and the clinical setting with no overall statistically significant clinical benefit, but there are individual successes that represent the promise of this approach. As cell-based vaccine technology continues to evolve, future studies can perhaps fulfill the potential that this exciting field of anti-cancer therapy holds.